Enhancing student engagement through role-playing: A study on reproductive system education in class IX E at SMP Negeri 5 Pontianak - Kartikasari, Euis (Jurnal Pendidikan Informatika dan Sains, 2024)
This study was conducted to determine the improvement in student activity and learning outcomes on the topic of the reproductive system in Class IX E at SMP Negeri 5 Pontianak. The objective of this research is to investigate the enhancement of student engagement and learning outcomes using the role-playing method. This classroom action research was carried out in two cycles. Data were collected through observation and tests. The results indicated an increase in student learning activities from 67.95% in the first cycle to 88.82% in the second cycle, as well as an improvement in learning mastery from 45.94% to 78.37%. Therefore, the role-playing method has proven to be effective in enhancing student activity and learning outcomes.